Interception Studies in Chir and Teak Plantations-new Forest - Dabral, B. G.; Subba Rao, B. K. (Indian Forester, 1968)
The paper presents the results of studies made on stemflow, throughfall and interception losses in a chir and teak plantation at Forest Research Institute Reserve Forest. It was seen that chir pine conducted 3.6, 74.3 and 22.1 per cent of gross rainfall as stemflow, throughfall and interception losses respectively for rainfall groups up to 2". The corresponding figures for all rainfall groups considered together were 8.8,69.7 and 27.0 per cent of gross rainfall. In teak 6.0, 73.2 and 20.8 per cent and 7.1, 64.1 and 28.8 per cent of rainfall were conducted as stemflow, throughfall and interception losses in respect of all rainfall groups combined together and for 0"-2" rainfall groups respectively. Since maximum number of trees in chir plantation fell within the diameter range 7.6 mm to 22.9 mm (3" to 9") it may be assumed that stemflow and interception losses ranged between 2 to 3.9 and 22-24% respectively of the total rainfall. The corresponding figures in respect of the teak plantation, where maximum. Number of trees were within diameter range of 15.2 mm to 30.5 mm (6" to 12") were 2.5 to 7.9 and 18:9 to 24.4 per cent of the total rainfall